2010
DOI: 10.1128/iai.00776-09
|View full text |Cite
|
Sign up to set email alerts
|

Major Surface Protease of Trypanosomatids: One Size Fits All?

Abstract: Trypanosomatids are a very diverse group of protozoa including many species of medical, veterinary, and/or economical importance. Leishmania spp. cause disease on the continents of Asia, Africa, Europe, and North and South America; Trypanosoma cruzi is the etiology of Chagas' disease in South and Central America; and Trypanosoma brucei infections result in African sleeping sickness. Four genera of heteroxenous trypanosomatids transmitted by insect vectors infect a wide range of hosts including humans, animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 110 publications
0
75
0
6
Order By: Relevance
“…The hydrolysis of HIV protease substrate by L. amazonensis extract was fully inhibited by pepstatin A and HIV protease inhibitors at 10 μmol/L, suggesting that an aspartic protease may be the parasite target of the inhibitors. Despite all these beneficial effects, the HIV protease inhibitors induced an increase in the expression of cysteine protease b (cpb) [19] and the metalloprotease gp63 [24] , two well-known virulence factors expressed by Leishmania spp., probably in an attempt to compensate the parasite aspartic protease inhibition [103] . Proposals of the molecular mechanisms of the aspartic protease inhibitors on the aspartic protease produced by microorganisms Direct actions -inhibition of aspartic proteases: The binding of the aspartic protease inhibitor to the active site of an aspartic protease blocks the binding of substrate to the enzyme.…”
Section: F Pedrosoimentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis of HIV protease substrate by L. amazonensis extract was fully inhibited by pepstatin A and HIV protease inhibitors at 10 μmol/L, suggesting that an aspartic protease may be the parasite target of the inhibitors. Despite all these beneficial effects, the HIV protease inhibitors induced an increase in the expression of cysteine protease b (cpb) [19] and the metalloprotease gp63 [24] , two well-known virulence factors expressed by Leishmania spp., probably in an attempt to compensate the parasite aspartic protease inhibition [103] . Proposals of the molecular mechanisms of the aspartic protease inhibitors on the aspartic protease produced by microorganisms Direct actions -inhibition of aspartic proteases: The binding of the aspartic protease inhibitor to the active site of an aspartic protease blocks the binding of substrate to the enzyme.…”
Section: F Pedrosoimentioning
confidence: 99%
“…Collectively, proteases participate in different steps of the multifaceted interaction events between microorganism and host structures, being considered as virulent attributes. Consequently, the biochemical characterization of these proteolytic enzymes is of interest not only for understanding proteases in general but also for understanding their roles in microbial infections and thus their exploitation as targets for rational chemotherapy of microbial diseases [3,6,10,[18][19][20][21][22][23][24] .…”
Section: Proteases Produced By Microorganisms: Global Functionsmentioning
confidence: 99%
“…This metallopeptidase produced by H. samuelpessoai cells shares common biochemical and immunological properties (Elias et al 2006;Santos et al 2006) with the major metallopeptidase expressed by Leishmania species, called leishmanolysin or gp63, a virulence factor that participates in different stages of the parasite life cycle such as adhesion and escape from host immune response (Yao, 2010). The incorporation of different proteinaceous substrates into SDS-PAGE demonstrated that leishmanolysin-like molecule from H. samuelpessoai was able to degrade hemoglobin, casein, immunoglobulin G, mucin, human and bovine albumins as well as the gut protein extract from Aedes aegypti (Figure 2) (Pereira et al 2010a), an experimental model to study the trypanosomatids-insect interplay (reviewed by Santos et al 2006), culminating in the generation of peptides and amino acids required for parasite growth and development, as well as it might cleave structural barriers in order to improve its dissemination.…”
Section: Identification Of Peptidases In Herpetomonas Spp and Possibmentioning
confidence: 99%
“…This peptidase is one of major surface molecules in all Leishmania species and play vital roles in the different stages of Leishmania life cycle, being suggested its participation in many aspects of the infection inside the mammalian host (Yao, 2010). The presence of a similar neutral-toalkaline metallopeptidase at the surface of C. fasciculata led to the suggestion that gp63 should not be involved in the infection of the mammalian host by Leishmania, but rather contributes to the survival of the trypanosomatid inside the digestive tract of the insect ).…”
Section: Peptidase Screening In Crithidiamentioning
confidence: 99%
“…On one hand, mammalian host environmental risk factors and genetic background influence the clinical manifestations of infection (4). On the other hand, parasite virulence determinants required for disease development include, but are not limited to, the major surface protease (MSP) (also called GP63 or leishmanolysin) and lipophosphoglycan (LPG) (5)(6)(7)(8). These two molecules play both overlapping and unique roles in pathogenesis.…”
mentioning
confidence: 99%